Fundamentals of ophthalmic dispensing – part 11: Single vision lens design part 2. Issue 8 (August 2020) - Black, Peter; Arbon Black, Tina
Abstract : In the second of their discussions of single vision lens design, Peter Black and Tina Arbon Black take a look at single vision aspheric and reduced aperture lens forms and consider related practical dispensing issues including field of view (C 76149, one distance learning CET point suitable for optometrists and dispensing opticians)